Photorealism with Twinmotion : Raster - Path Tracer - Lumen - Rodolfi, Luca, ....- (Troutdale : Luca Rodolfi, 2023)
Dive deep into the world of photorealism with Twinmotion, the groundbreaking software (based on Unreal Engine 5) that's reshaping the 3D rendering landscape. This comprehensive guide not only introduces you to the core principles and capabilities of Twinmotion but also helps you master its three potent engines: Raster, Path Tracer, and Lumen. You'll gain insights into the importance of photorealism in today's visual era and how it holds a significant place in modern design and presentation. The book doesn't stop there. It takes you on a journey through crafting photorealistic interiors and exteriors, aptly referred to as ArchViz techniques. You'll learn to design intricate urban environments that include lifelike cities, structures, and vehicles. Nature lovers aren't left behind as the guide delves into simulating vibrant oceans, capturing the majesty of mountains, and rendering the lushness of dense forests and greenery. For those who love venturing into the realms of imagination, the book offers a passage into the worlds of sci-fi, history, and the neon-lit streets of cyberpunk. Moreover, it provides expert guidance on adapting to diverse environmental conditions, ensuring your renderings are perfect, be it a serene daytime setting or a rainy nighttime ambiance. Whether you are an architect, a designer, or someone deeply passionate about 3D graphics, this book serves as your bridge to achieving unparalleled photorealism. With Twinmotion as your tool and this guide as your companion, you won't just be imagining – you'll be creating masterpieces.
Keywords: 3D.; Photorealism